Synthesis, crystal structure, and electrochemical hydrogenation of the La2Mg17-xMx (M = Ni, Sn, Sb) solid solutions - Kordan, Vasyl; Nytka, Vitalii; Tarasiuk, Ivan; Zelinska, Oksana; Pavlyuk, Volodymyr (European Journal of Chemistry, 2021)
The crystal structure of La2Mg17-xSnx solid solution was determined by single crystal X-ray diffraction for the first time. This phase crystallizes in hexagonal symmetry with space group P63/mmc (a = 10.3911(3), c = 10.2702(3) Å, V = 960.36(6) Å3, R1 = 0.0180, wR2 = 0.0443 for the composition La3.65Mg30Sn1.10) and is related to the structure of CeMg10.3 and Th2Ni17-types which are derivative from the CaCu5-type. A series of isotypical solid solutions La2Mg17-xMx (M = Ni, Sn, Sb, x ~0.8) was synthesized and studied by X-ray powder diffraction, energy dispersive X-ray spectroscopy and fluorescent X-ray spectroscopy. All solid solutions crystallize with the structure related to the Th2Ni17-type. The electrochemical hydrogenation confirmed the similar electrochemical behavior of all studied alloys. The amount of deintercalated hydrogen depends on the physical and chemical characteristics of doping elements and increases in the sequence Sn < Mg < Sb < Ni. The most geometrically advantageous sites are octahedral voids 6h of the initial structure, thus a coordination polyhedron for H-atom is an octahedron [HLa2(Mg,M)4].